Reduction Levels and the Effects of High-Molecular-Weight Adiponectin via AMPK/eNOS in Chinese Type 2 Diabetes - Lian, K.; Guo, X.; Huang, Q.; Tan, Z.; Xia, C.; Wang, R.; Yi, F.; Li, W.; Liu, J.; Li, Y.; Guo, S.; Wang, H.; Ji, Q.; Tao, L. (Experimental and Clinical Endocrinology & Diabetes, 2016)
Aim: This study was to investigate the change of high-molecula-weight (HMW) adiponectin (APN) isoform, the association between type 2 diabetes mellitus (T2DM) and HMW APN isoform, the variation of Disulfide-bond A oxidoreductase-like protein (DsbA-L), the effect of HMW APN isoform on AMP-dependent protein kinase (AMPK) and endothelial nitric oxide synthase (eNOS) in Chinese T2DM.Method: 169 patients aged at (48.7±9.4) years and 107 healthy control subjects aged at (42.6±7.8) years took part in this study. Anthropometric measures of the characters were assayed and different APN isoforms, DsbA-L, AMPK and eNOS levels were determined.Results: Ln(sRAGE) and Ln(Adiponectin) were significantly lower and significantly higher for the other characteristics in T2DM. Ln(Adiponectin) was negatively and significantly correlated with WHR, Ln(triglycerides), fasting plasma glucose, HbA1c (%) in control subjects and T2DM patients. Plasma and adipose tissue total APN and HMW APN were significantly reduced in newly diagnosed T2DM patients. DsbA-L was markedly down-regulated in diabetic adipose tissue. HMW APN caused significant decreases in AMPK and eNOS phosphorylation levels of human umbilical vein endothelial cells (HUVECs).Conclusions: Our results demonstrated that total APN levels was closely related to the risk of T2DM and HMW APN reduction was involved in the diabetic vascular AMPK/eNOS signal pathway. The findings will provide insight into novel therapeutic approaches for reducing the elevated cardiovascular risk associated with T2DM.
Keywords: HMW adiponectin; DsbA-L; AMPK/eNOS; diabetes